Managing strategic buyers: should a seller ban resale? - Beccuti, Juan (2016)
We study the seller’s pricing strategy of one good (finite inventory) that can be sold in two bargaining periods (before a deadline) when she faces two strategic buyers with private valuations. In particular, we are interested in comparing the outcomes of this game in two environments: allowing versus forbidding a resale option. Without resale, the seller charges prices high in the first bargaining period to motivate high valuation consumers to buy, but prices are reduced if no buyer expresses their willingness to buy. Compared with this benchmark case, introducing the resale option generates two effects: there is an increase in consumers willingness to buy in the first period, motivating an increase in the price of the first period, but there is an increase in demand price-elasticity of the first period, motivating a decrease in the price of the first period. We show that the second effect dominates for a bunch of reasonable parameters, motivating a reduction in first period price and generating an increase in profits, aggregate consumer surplus, and, thus, in welfare